The Vigor of Defense Against Non-Self: Potential Superiority of Allorestricted T Cells in Immunotherapy of Cancer? - Burdach, Stefan; Kolb, Hans-Jochem (Frontiers in Oncology, 2013)
Men and sharks are both jawed vertebrates at the top of the food chain. Sharks are the first extant to develop adaptive immunity preserved to man throughout jawed vertebrates. We hy-pothesize here, that T cell receptor / major histocompatibility complex (TCR/MHC) interac-tions developed as the defense mechanism of carnivors against takeover by their victims‘ cells derived pathogens. Germline encoded TCR segments have been conserved in evolution, providing the MHC bias of TCR. Ancestor genes of MHC polymorphisms may have first de-veloped as a mating preference system, that later in evolution provided host immune respons-es destroying infectious nonself, yet maintaining tolerance to self. Pathogens may thus have simultaneously selected for alloimmunity. Allorejection has been observed in sharks and men. Cannibalism is a common ecological in-teraction in the animal kingdom, especially prevalent in aquatic communities; it favours selec-tion of intraspecies allo responses for defence of self integrity. Alloreactive T-cells do not undergo negative selection of strong TCR/MHC interactions; thus, they react stronger than self-MHC recognizing T cells. High levels of genetic diversity at MHC genes play a critical role in protecting populations of vertebrate species from contagious cells displaying stemness and homing features, including cancer cells. Recognition of self-MHC fails especially in dis-eases, which predominantly arise with age and after the peak of reproduction, e.g. cancer. So far, the treatment of malignant disease with autologous T-cells has widely failed. Allorecogni-tion constitutes an extremely powerful mechanism in evolution, which may be employed in immunotherapy of cancer by MHC disparate, e.g. haploidentical transplantation and consecu-tive treatment with T cells from the donor parents recognizing tumor selective peptides pre-sented by the non-inherited haplotype on the tumor.